2017
DOI: 10.1016/j.kjms.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profile analysis of long non‐coding RNAs in thoracic aortic aneurysm

Abstract: Thoracic aortic aneurysm (TAA) is a highly lethal vascular disease. Long non-coding RNAs (lncRNAs) are newly discovered as a regulator of protein genes and play critical roles in cardiovascular physio-pathological processes. However, there were a few studies looking at lncRNAs in TAA. In this study, we profiled differential expression of lncRNAs between TAA (TAA group, N = 6) and normal thoracic aorta (control group, n = 6) by third-generation lncRNA microarray. We identified 1352 up-regulated and 1624 down-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In another study, lncRNA MALAT1 was also reported to interact with BRG1 to regulate the function of smooth muscle in TAA [14]. Moreover, a recent microarray study revealed a large number of differentially expressed lncRNAs in TAA [15]. Giver participates in inflammation, oxidative stress, and proliferation in vascular smooth muscle cells, which are involved in TAA [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, lncRNA MALAT1 was also reported to interact with BRG1 to regulate the function of smooth muscle in TAA [14]. Moreover, a recent microarray study revealed a large number of differentially expressed lncRNAs in TAA [15]. Giver participates in inflammation, oxidative stress, and proliferation in vascular smooth muscle cells, which are involved in TAA [12].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary deep sequencing suggested the positive correlation between Giver and LOXL1-AS in TAA. It is known that lncRNAs participate in human diseases mainly by interacting with downstream effector pathways [16,17]. Studies on the interaction between different lncRNAs are rare.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-related VSMC dysfunction and ECM degradation were suggested as potential mechanisms according to recent data. Microarray profile analysis revealed that hundreds and thousands of lncRNAs are involved in human thoracic aortic aneurysm (TAA) development, such as Lnc-HLTF-5 [44], HIF1A-AS1, RP11-465L10.10, and CTD-2184D3.5 [45], which might play roles in regulating the expression of MMP-9 in aortic tissue and then facilitate the expansionary remodeling. HIF1alpha-antisense RNA 1 (HIF1A-AS1) was the first reported lncRNA participating in TAA pathogenesis [46].…”
Section: The Regulatory Role Of Lncrna In Cardiac Remodelingmentioning
confidence: 99%
“…More recently, Li et al [64] profiled differential expression of lncRNAs between TAA and normal aortic samples by microarray analysis. Through different filtering steps, the authors selected two TAA-related lncRNAs (RP11-465L10.10 and CTD-2184D3.5) and elaborated their relationship with protein-coding genes, thus providing insights into the research of novel biomarkers and therapeutic targets for TAA [64].…”
Section: Novel Potential Biomarkers: Long Non-coding Rnas and Circular Rnasmentioning
confidence: 99%